An Empirical Analysis of the Factors Associated with Mushroom Cultivation: A Case of Dhaka - Rahman, Mehnaj; Islam, Nazrul; Saha, Sajeeb; Haq, Iqramul; Hossain, Md. Ismail (Asian Business Review, 2022)
The analysis aimed to identify mushroom production and marketing problems by different stakeholders in Bangladesh, specifically in the Dhaka district. It also seeks to improve the mushroom marketing system for domestic markets. The research was carried out in the Savar Upazila, located in the Dhaka district. One hundred twenty-one farmers were randomly picked and asked questions using an interview schedule to collect data. Pearson’s chi-squared test was utilized to investigate the degree to which socio-demographic factors and the response variable are related. In the end, a multivariate method known as logistic regression analysis is used to study the relationships between each predictor variable and the result variable that pertains to the respondents. The result revealed significant effects of gender, farmer’s education, and information sources for intermediate and experienced mushroom cultivators. However, land size, scientific cultivation, sources of capital, packaging, and sale were stronger among expert mushroom farmers than the new and mediocre mushroom farmers. This research provides valuable insights to improve the mushroom marketing system for domestic markets.